Fungsi Upacara Adat Ngensudah pada Masyarakat Dayak Melahui di Kabupaten Melawi - Dwi Oktariani; Aline Rizky Oktaviari; Anggela Dhea Natasia (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
This research aims to understand the ritual processes of death in the tribal community of Dayak Melahui as social cultural values. This research employs the ethnographic method as a qualitative descriptive approach. Data analysis techniques include data collection, reduction, data presentation, and inference. The research findings showed that Ngensudah's customary ritual process included events such as Nyengkolat'n, tomb renovation, statue installation, Ompong cutting, Bigal Dance, animal sacrifice cutting, grave worship, Kerongkang Ritual, Bigall Dance, and Pampali Tuak Opening. The maintenance of customary ceremonies involves both spiritual and social functions. The values contained in customary ceremonies include gotong-royong values, responsibility, leadership, solidarity, cultural wisdom, love of the homeland, religious values, and means in harmony with customary norms.